Should non-disclosures be considered as morally equivalent to lies within the doctor–patient relationship?. Issue 10 (22nd July 2016) - Cox, Caitriona L; Fritz, Zoe
Abstract : In modern practice, doctors who outright lie to their patients are often condemned, yet those who employ non-lying deceptions tend to be judged less critically. Some areas of non-disclosure have recently been challenged: not telling patients about resuscitation decisions; inadequately informing patients about risks of alternative procedures and withholding information about medical errors. Despite this, there remain many areas of clinical practice where non-disclosures of information are accepted, where lies about such information would not be. Using illustrative hypothetical situations, all based on common clinical practice, we explore the extent to which we should consider other deceptive practices in medicine to be morally equivalent to lying. We suggest that there is no significant moral difference between lying to a patient and intentionally withholding relevant information: non-disclosures could be subjected to Bok's 'Test of Publicity' to assess permissibility in the same way that lies are. The moral equivalence of lying and relevant non-disclosure is particularly compelling when the agent's motivations, and the consequences of the actions (from the patient's perspectives), are the same. We conclude that it is arbitrary to claim that there is anything inherently worse about lying to a patient to mislead them than intentionally deceiving them using other methods, such as euphemism or non-disclosure. We should question our intuition that non-lying deceptive practices in clinical practice are more permissible and should thus subject non-disclosures to the same scrutiny we afford to lies.